PENGARUH AKUNTABILITAS, TRANPARANSI, DAN PENGAWASAN TERHADAP PENGELOLAAN ANGGARAN BERKONSEP VALUE FOR MONEY DENGAN STANDAR AKUNTANSI PEMERINTAHAN SEBAGAI VARIABEL MODERATING (STUDI EMPIRIS PADA SKPD KOTA PEKANBARU) - Anggraini, Raja Rika; Agusti, Restu; Paulus, Sem (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this study was to determine and analyze the influence of accountability, transparency, oversight of the budget management concept of value for money with government accounting standards in government agencies. And to investigate and analyze the possibility of government accounting standards could strengthen or weaken the relationship between accountability, transparency and oversight to the budget management concept of value for money. The population of this research is SKPDPekanbaru a total of 43government agencies, the sampling technique using purposive sampling so that the eligible sample were as many as 172 persons. Data analysis method used is multiple linear regression analysis using SPSS 23 for windows. It can be concluded that the variables of public accountability, public transparency and scrutiny affect the budget management concept of value for money in government agencies. Variables public accountability with government accounting standards as moderating variables affect the budget management of the concept of value for money in government agencies. Variables public transparency in government accounting standards as moderating variable does not affect the budget management concept of value for money in government agencies. Variable surveillance with government accounting standards as moderating variables affect the budget management of the concept of value for money in government agencies.Keyword : Accountability, Transparency, Oversight, Budget Management concept Value For Money, Government Accounting Standards